Resolvin D1 and D2 reduce SARS‐CoV‐2‐induced inflammatory responses in cystic fibrosis macrophages. Issue 4 (22nd March 2021) - Recchiuti, Antonio; Patruno, Sara; Mattoscio, Domenico; Isopi, Elisa; Pomilio, Antonella; Lamolinara, Alessia; Iezzi, Manuela; Pecce, Romina; Romano, Mario
Abstract: An excessive, non‐resolving inflammatory response underlies severe COVID‐19 that may have fatal outcomes. Therefore, the investigation of endogenous pathways leading to resolution of inflammation is of interest to uncover strategies for mitigating inflammation in people with SARS‐CoV‐2 infection. This becomes particularly urgent in individuals with preexisting pathologies characterized by chronic respiratory inflammation and prone to bacterial infection, such as cystic fibrosis (CF). Here, we analyzed the immune responses to SARS‐CoV‐2 virion spike 1 glycoprotein (S1) of macrophages (MΦ) from volunteers with and without CF and tested the efficacy of resolvins (Rv) D1 and D2 in regulating the inflammatory and antimicrobial functions of MΦ exposed to S1. S1 significantly increased chemokine release, including interleukin (IL)‐8, in CF and non‐CF MΦ, while it enhanced IL‐6 and tumor necrosis factor (TNF)‐α in non‐CF MΦ, but not in CF cells. S1 also triggered the biosynthesis of RvD1 and modulated microRNAs miR‐16, miR‐29a, and miR‐103, known to control the inflammatory responses. RvD1 and RvD2 treatment abated S1‐induced inflammatory responses in CF and non‐CF MΦ, significantly reducing the release of select chemokines and cytokines including IL‐8 and TNF‐α. RvD1 and RvD2 both restored the expression of miR‐16 and miR‐29a, while selectively increasing miR‐223 and miR‐125a, which are involved in NF‐κB activation and MΦ inflammatory polarization. During Pseudomonas aeruginosa infection, S1 stimulated the MΦ phagocytic activity that was further enhanced by RvD1 and RvD2. These results provide a map of molecular responses to SARS‐CoV‐2 in MΦ, key determinants of COVID‐19‐related inflammation, unveiling some peculiarity in the response of cells from individuals with CF. They also demonstrate beneficial, regulatory actions of RvD1 and RvD2 on SARS‐CoV‐2‐induced inflammation.